Islamic Counseling for The Prevention of Game Addiction: Case Study in Elementary School - Aprilia Zuliaty; Syamsul Bakhri; Muhamad Rifa'i Subhi (State Islamic University (UIN) Salatiga, 2023)
Game addiction is a problem that gets much attention and is often discussed by the public. Currently, much research focuses more on prevention efforts for gaming addiction. The rapid development of technology will undoubtedly have negative impacts, including the development of technology, leading to elementary school children being vulnerable to games. This article examines various alternatives to prevent game addiction, especially for elementary school children easily influenced by fun things like games. The method used in this research is descriptive qualitative research location, namely Majlis Darul Ishlah, North Pekalongan, with research subjects being children aged 10-12 years. Conducting interviews, observation, and documentation uses a case study approach. The research that has been carried out has shown that Islamic counseling can significantly reduce gaming addiction in elementary school children, with a good increase in academic achievement and increased social interaction.